1176 Paediatric Patients Presented with Right Iliac Fossa Pain: Is the Ultrasound Scan Conducted in A Timely Manner?. (12th October 2021) - Barghash, M; Iskandar, A; Fawzy, S; Ali, B
Abstract: Aim: Ultrasound scan is a crucial clinical tool in the management of acute appendicitis in children. That is because it can aid in the diagnosis without exposing the patient to potentially harmful ionising radiation from computed tomography scans. In this project, we were assessing whether children presented with right iliac fossa pain receive their scans on time. In addition, we were exploring whether definitive management and hospital length of stay were affected by the scan delay. Method: This was a retrospective project in which we assessed case notes of paediatric patients who had an ultrasound scan between September 2019 and September 2020 in one of the district general hospitals in the UK. The project included notes of patients who were below 16, admitted with right iliac fossa pain, and had an inpatient ultrasound scan. Results: A total of 33 patients met the inclusion criteria. The waiting time ranged from 1 hour to 89 hours with a mean of around 19.5 hours and a median of 14.5 hours. The hospital length of stay ranged from 1 day to 21 days with a mean of around 2.5 days and a median of 1 day. Conclusions: An ultrasound scan should be conducted within the same day of admission for all paediatric patients presented with right iliac fossa pain.